1998
DOI: 10.1029/98gl00758
|View full text |Cite
|
Sign up to set email alerts
|

A substorm model with onset location tied to an auroral arc

Abstract: Abstract.Two important observational constraints on substorm onset theories are that (1) substorm onset occurs on field lines of a pre-existing auroral arc, and (2) reduction of the cross-tail current occurs in the near-Earth magnetotail. Recent progress in linking generation of at least some auroral arcs to field line resonances (FLRs) and current disruption to possibly the cross-field current instability (CCI) suggests a synergistic combination of these two theories. We suggest that as the cross-tail current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“… Akasofu [1964] and Lui and Murphree [1998] showed on the basis of ground‐based auroral observations that substorm initial brightening starts at a point in the preexisting auroral arc. On the other hand, Lyons et al [2002] claimed that an auroral breakup does not generally occur along one of the preexisting arcs but instead occurs along a thin breakup arc that forms equatorward of all growth phase arcs a few minutes prior to onset.…”
Section: Discussionmentioning
confidence: 99%
“… Akasofu [1964] and Lui and Murphree [1998] showed on the basis of ground‐based auroral observations that substorm initial brightening starts at a point in the preexisting auroral arc. On the other hand, Lyons et al [2002] claimed that an auroral breakup does not generally occur along one of the preexisting arcs but instead occurs along a thin breakup arc that forms equatorward of all growth phase arcs a few minutes prior to onset.…”
Section: Discussionmentioning
confidence: 99%
“…However, was it actually part of the process of triggering the substorm? For example, Lui and Murphree (1998) recently proposed that cross-tail current disruption occurs via the cross-field current instability (CCI) when the current is driven to a critical value during an appropriate half-cycle of a MHD field-line resonant wave. This occurs at the inner edge of the plasma sheet, near where AWFCs occur.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been suggested that plasma instabilities are responsible for the perturbations of these field lines, driven by large plasma pressure gradients in the neighborhood of the equatorial plane where the field line curvature is large. 2,3 In fact the suggestion that plasma pressure driven instabilities operate in the geosynchronous substorm region of the magnetosphere goes back much further to an earlier publication by Roux et al 4 At 6-10 Earth radii, the magnetospheric plasma is essentially collisionless and the plasma beta ͑␤͒ at the equatorial plane is typically larger than unity ͑␤ϭ8p/B 2 Ͼ1 where p is the plasma pressure and B the magnetic field magnitude͒. Thus, to test the relevance of the above-given suggestion, it is necessary to establish the conditions required for the onset of plasma instabilities in collisionless high beta magnetic dipole configurations and to determine whether such conditions are met in the Earth's magnetosphere.…”
Section: Introductionmentioning
confidence: 99%